I don't want to be a rule enforcer during the COVID-19 pandemic: Frontline employees' plight. (November 2021) - Northington, William Magnus; Gillison, Stephanie T.; Beatty, Sharon E.; Vivek, Shiri
Abstract: This research explores the pandemic-related experiences of frontline employees (FLEs) relative to customer rule-enforcement interactions within retail and service industries. Using a survey, incorporating closed-ended and CIT questions, we investigated, from the FLEs' perspectives, the occupational stress of rule-enforcement, company expectations of FLEs regarding rule enforcement, and the emotional impact of customer interactions on FLEs. Results indicate that several customer misbehaviors, such as not following rules and being rude, produce significant occupational stress. Further, based on our CIT assessments, many of the FLEs' recounted rule-enforcement incidents involved negative customer reactions, translating to heightened negativity for FLEs due to emotional contagion.